2020
DOI: 10.1093/cid/ciaa1160
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormone Therapy and Tenofovir Diphosphate Concentration in Dried Blood Spots: Primary Results of the Interactions Between Antiretrovirals And Transgender Hormones Study

Abstract: Background Pilot studies showed lower tenofovir plasma concentrations during PrEP use among transgender women (TGW) using feminizing hormones compared with cisgender men (CGM). Tenofovir diphosphate (TFV-DP) concentrations in TGW and transgender men (TGM) using gender affirming hormones and on directly observed dosing of PrEP have not been studied. Methods TGM and TGW on at least 6 months of stable sex hormone therapy contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…Three recent trans-centred studies reported that the use of feminizing hormones was associated with reduced PrEP concentrations in blood, suggesting that the reduced efficacy of oral PrEP is not merely the result of lower adherence amongst transgender women [47][48][49]. Another recent study assessing the drug interactions between sex hormone therapy and oral PrEP showed that tenofovir concentrations were comparable between transgender women and cisgender men, but not between transgender men and cisgender women, although all participants were projected to reach protective PrEP levels [50]. Furthermore, a secondary analysis of iPrEx trial data showed that significant differences in baseline characteristics between transgender women and cisgender MSM (e.g.…”
Section: Moving From Trans-subsumed To Trans-centred Researchmentioning
confidence: 99%
“…Three recent trans-centred studies reported that the use of feminizing hormones was associated with reduced PrEP concentrations in blood, suggesting that the reduced efficacy of oral PrEP is not merely the result of lower adherence amongst transgender women [47][48][49]. Another recent study assessing the drug interactions between sex hormone therapy and oral PrEP showed that tenofovir concentrations were comparable between transgender women and cisgender men, but not between transgender men and cisgender women, although all participants were projected to reach protective PrEP levels [50]. Furthermore, a secondary analysis of iPrEx trial data showed that significant differences in baseline characteristics between transgender women and cisgender MSM (e.g.…”
Section: Moving From Trans-subsumed To Trans-centred Researchmentioning
confidence: 99%
“…Transgender women on feminising hormonal treatment were thought to be in danger of drug–drug interactions with reduced efficacy of PrEP; however, a recent study has shown this is not the case. 45 …”
Section: Quick Facts On Oral Pre-exposure Prophylaxismentioning
confidence: 99%
“…Transgender women on feminising hormonal treatment were thought to be in danger of drug-drug interactions with reduced efficacy of PrEP; however, a recent study has shown this is not the case. 45 Tenofovir disoproxil fumarate is largely eliminated by the kidneys. There are few drug interactions of note, but TDF should be used with caution with medications that cause renal toxicity (see Table 3).…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…In addition, transgender women are still a very hidden population in China, thus, intervention delivery through social media, including mobile apps may also needed [ 28 ]. In addition to traditional interventions such as health education and condom use, newer strategies such as pre-exposure prophylaxis should also consider to include transgender women [ 55 , 56 ] to ensure that this population in China are not left behind.…”
Section: Discussionmentioning
confidence: 99%